2015
DOI: 10.1002/etc.3097
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of chromium stress‐responsive micro RNAs and their target genes in tobacco (Nicotiana tabacum) roots

Abstract: Tobacco easily accumulates certain heavy metals in leaves and thus poses a potential threat to human health. To systematically dissect Cr-responsive microRNAs (miRNAs) and their targets at the global level, 4 small RNA libraries were constructed from the roots of Cr-treated (Cr) and Cr-free (control) for 2 contrasting tobacco genotypes,Yunyan2 (Cr-sensitive) and Guiyan1 (Cr-tolerant). Using high-throughput-sequencing-technology, the authors identified 53 conserved and 29 novel miRNA families. Comparative genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 43 publications
2
19
0
1
Order By: Relevance
“…A differential expression pattern was observed only for the miR6149 family, whose expression remained unchanged in Guiyan1, but was suppressed in Yunyan2. Differential regulation of 14 novel miRNA families was also reported in the two genotypes under Cr toxicity (Bukhari et al 2015). This validates the important functions played by miRNAs in regulating heavy metal stress tolerance in plants.…”
Section: Barciszewskasupporting
confidence: 52%
See 1 more Smart Citation
“…A differential expression pattern was observed only for the miR6149 family, whose expression remained unchanged in Guiyan1, but was suppressed in Yunyan2. Differential regulation of 14 novel miRNA families was also reported in the two genotypes under Cr toxicity (Bukhari et al 2015). This validates the important functions played by miRNAs in regulating heavy metal stress tolerance in plants.…”
Section: Barciszewskasupporting
confidence: 52%
“…In the same plant, the targets for miR156, miR159, miR833a, and miR396 were depicted to be SPL, TCP, RAX2, and GRF, respectively . Cr stress Bukhari et al (2015) recently identified 53 conserved and 29 miRNA families from the four sRNA libraries constructed from Cr-treated and Cr-free (control) roots of two contrasting tobacco genotypes, Yunyan2 (Cr-sensitive) and Guiyan1 (Cr-tolerant). The authors observed that 11 conserved miRNA families were up-regulated in Guiyan1; however, their expression pattern exhibited no significant changes in Yunyan2.…”
Section: Barciszewskamentioning
confidence: 99%
“…Using GenBank (http://www.ncbi.nlm.nih.gov/) and Rfam 10.1 (http://rfam.sanger.ac.uk) databases comparison, non-coding RNAs such as ribosomal RNA (rRNA), transfer RNA (tRNA), small nuclear RNA (snRNA), snoRNA, and signal recognition particle RNA (srpRNA) were identified and removed. The remaining sRNAs were subjected to a Basic Local Alignment Search Tool (BLASTn) search with no more than two mismatches against miRBase 18.0 database (http://www.mirbase.org/) to identify known miRNA in the samples [44, 45]. sRNA annotation followed a priority rule for classification to avoid redundancy: non-coding RNA (in which GenBank > Rfam) > known miRNA > repeat [46].…”
Section: Methodsmentioning
confidence: 99%
“…Cotton seedlings treated with Pb showed downregulation of miR156, miR398, miR399 and upregulation of miR162, miR167, miR169, miR395, miR396, and miR397 (He et al, 2014 ). Chromium showed upregulation of miR156, miR167, miR169, miR171, and downregulation of miR166 (Bukhari et al, 2015 ) (Figure 3 ). Among the heavy metal responsive miRNAs, miR156, miR159, miR166, and miR398 were shown to be differentially regulated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that various conserved miRNAs are differentially regulated during the normal and stress conditions (Figure 3 ). Differential expression of miRNAs in heavy metal stress indicates the possible involvement of miRNAs in heavy metal stress detoxification and tolerance (Ding et al, 2011 ; Liu and Zhang, 2012 ; Zhou et al, 2012 ; Bukhari et al, 2015 ; Noman and Aqeel, 2017 ). Here, we have focused on studies showing differential expression of conserved miRNA in metal stress and regulation of signaling pathway by miRNAs or vice versa in response to heavy metals.…”
Section: Introductionmentioning
confidence: 99%